A predictive model to differentiate the fruit bats cynopterus brachyotis and C. cf. brachyotis forest (Chiroptera: Pteropodidae) from Malaysia using multivariate analysis - Jayaraj V.K; Charlie J. Laman; Abdullah M.T (2012)
A predictive model to differentiate the fruit bats Cynopterus brachyotis and C. cf. brachyotis Forest (Chiroptera: Pteropodidae) from Malaysia using multivariate analysis. Zoological Studies 51(2): 259-271. Field discrimination of Cynopterus brachyotis and C. cf. brachyotis Forest (as designated by Francis 2008) in southern Thailand, Peninsular Malaysia, and Borneo is problematic. These 2 forms are sympatric in this region but are confined to different habitat types: C. brachyotis inhabits open habitats, orchards, and agricultural areas, while C. cf. brachyotis Forest is confined to primary and old secondary forests. In this study, we attempted to develop prediction models to identify both C. brachyotis and C. cf. brachyotis Forest in this region based on multivariate statistics. Two predictive models were generated using a canonical discriminant function, and it was found that 5 characters can be used to accurately identify museum vouchers of C. brachyotis and C. cf. brachyotis Forest. Four characters are needed for field identification of these 2 forms of Cynopterus in southern Thailand, Peninsular Malaysia, and Borneo. A review of the current taxonomy and classification indicated that there is a need to describe the 6 existing forms of the C. brachyotis complex in the Indo-Malayan region. This will aid conservationists, field ecologists, and taxonomists in taxonomic- and conservation-related decisions about this species complex. http://zoolstud.sinica.edu.tw/Journals/51.2/259.pdf